A comparison study of different acid pretreatment technique on the removal of lignin and reducing sugar production from different biomass / Mohamed Fittri Mohamed Rosedi and Dr. Siti Sabrina Mohd Sukri - Mohamed Rosedi, Mohamed Fittri; Mohd Sukri, Siti Sabrina (2020)
Lignocellulosic biomass included rice husks, corn cobs, oil palm, sugarcane bagasse, and bamboo are one of the abundant organic resources in most Asian countries. It basically consists of three fractions, cellulose, hemicelluloses, and lignin. The improper disposal method of biomass, such as open burning has led to environmental problems because of the smoke released to the air and reduced air quality. With that, pretreatment steps are required to make each fraction available for further use. This study was designed to compare the efficiency of sulphuric acid, H2SO4 and hydrochloric acid, HCl pretreatment on the removal of lignin, and total reducing sugar (TRS) production from different biomass. Since it is a comparative study, the data information was collected based on the previous study from Science Direct, Course Hero, Google Scholar, Sci-Hub, and Researh Gate. Determination of lignin removal by using Kappa Number and reducing sugars by 3,5-dinitrosalicylic acid (DNS) method was used. The input variables for each sample consisted of acid concentration, temperature, and solid loading in the range of 1% - 10%, 45˚C - 180˚C, and 1:1-1:10, respectively. The highest lignin removal is pretreated corn cobs that reduced to 90% lignin removal from 0.074g to 0.0085g/g after pretreatment. Process optimisation gave reducing sugar yields of 0.0751 and 0.096 g/L (rice husks), 24.7 and 81.8 g/L (corn cobs), 1.81 and 2.7 g/L (oil palm), 3.67 and 89.4 g/L (sugarcane bagasse), 0.319 and 0.93 g/L (bamboo) for H2SO4 and HCl pretreatments respectively. The maximum TRS yield reported about 89.4 g/L, sugarcane bagasse because the ability of HCl to permeate the lignocellulosic biomass more easily compared to H2SO4 pretreatment methods. The highest percentage of cellulose (corn cobs, 90.4%) was also observed with the HCl model. Besides, the optimised HCl pretreatment showed high efficiency at releasing reducing sugars from pretreated biomass.